Expression and Significance of WNT4 in Ectopic and Eutopic Endometrium of Human Endometriosis. (March 2016) - Liang, Yanming; Li, Yan; Liu, Kuiran; Chen, Peng; Wang, Danbo
The objective was to investigate the expression of the WNT4 gene in ectopic endometrium and eutopic endometrium (EU) during endometriosis and the relationship of WNT4 expression with the menstrual cycle. Ectopic endometrium and EU tissues were collected from 30 women with pathologically confirmed endometriosis and 30 women without endometriosis. The WNT4 protein and messenger RNA (mRNA) expression levels were measured by fluorescence-based quantitative real-time polymerase chain reaction, immunohistochemistry, and Western blot methods. The expression of WNT4 was not significantly correlated with the menstrual cycle, and there were no significant differences when WNT4 expression in proliferative endometrium was compared with that in secretory endometrium within each group. There were no significant differences between the protein and mRNA expression of WNT4 in ectopic endometrium and in EU from participants with endometriosis. The WNT4 expression level in EU was significantly reduced compared with that in normal endometrium of the control group, even when analyzed by the menstrual cycle phase. WNT4 was also downregulated in ectopic lesions. This study provides further evidence supporting the theory of "EU determinism" in the pathogenesis of endometriosis.